2023
DOI: 10.3390/ijms24119279
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of Immune Cells and Platelets in an Ovarian Cancer Microenvironment and Their Prognostic Significance

Abstract: Ovarian cancer (OC) is one of the deadliest gynecological cancers, largely due to the fast development of metastasis and drug resistance. The immune system is a critical component of the OC tumor microenvironment (TME) and immune cells such as T cells, NK cells, and dendritic cells (DC) play a key role in anti-tumor immunity. However, OC tumor cells are well known for evading immune surveillance by modulating the immune response through various mechanisms. Recruiting immune-suppressive cells such as regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 295 publications
0
2
0
Order By: Relevance
“…A substantial information exchange occurs in the circulation between tumor cells, immune cells and circulating platelets (TEPs) ( 25 - 27 ). One study reported that PD-L1 mRNA expression in plasma-derived exosomes could help predict the clinical responses of melanoma or NSCLC patients who received anti-PD-1 therapy ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial information exchange occurs in the circulation between tumor cells, immune cells and circulating platelets (TEPs) ( 25 - 27 ). One study reported that PD-L1 mRNA expression in plasma-derived exosomes could help predict the clinical responses of melanoma or NSCLC patients who received anti-PD-1 therapy ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…18 Platelets are involved in immune evasion by interactions with tumor cells or through the secretion of a variety of growth factors and cytokines to promote tumor growth and angiogenesis. 19 The serum albumin level is an indicator of nutritional status. Hypoalbuminemia may occur as a systemic inflammatory response and reflects malnutrition or cachexia because of tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Research has highlighted the prognostic value of TAMs in OC, particularly through the assessment of ratios like M1/M2 and M2/TAMs. However, the overall density of TAMs in ovarian tumors has not demonstrated significant prognostic significance [6,8,27,[41][42][43].…”
Section: Role Of Tumor Microenvironment In Ovarian Cancer Progressionmentioning
confidence: 99%
“…TGFβ plays a key role in polarizing TANs, suppressing N1, and promoting N2 phenotypes. However, the functional plasticity of TANs in human OC is not well studied [6,42,46,47].…”
Section: Role Of Tumor Microenvironment In Ovarian Cancer Progressionmentioning
confidence: 99%